Answer:
1: y intercept = 5
2: y interpcept = -2
3: y intercept = -3
Step-by-step explanation:
So for the 1st and 3rd ones (the graphs), all you have to do is find which y matches the x value of 0
The 2nd one is a bit harder. I’ll explain it the best I can
So in the y section, you see that -4 goes to -3 when the x is raised by 1. There for everytime the x raises by 1, so does the y. That means when x = 0, the y = -2
To find the product of <span>-2x^3+x-5 and x^3-3x-4, we need to multiply each term in the first polynomial by the second polynomial. (So, x^3 - 3x - 4) times ....
-2x^3 = -2x^6 + 6x^4 + 8x^3
x = x^4 - 3x^2 - 4x
-5 = -5x^3 + 15x + 20
If we add all these together, we get (-2x^6 + 7x^4 + 3x^3 - 3x^2 + 11x + 20)</span>
If your original equation was , then a reflection over the x-axis means you need all the y-values to switch sign. This means you need to multiply that function by -1.
or
79-y=2y+22
Add y on both sides
79=3y+22
Subtract 22 from both sides
57=3y
Divide by 3 on both sides
19=y